A Study of Chiggers, Rodents and Infection Rate of Rickettsia in Rodents from Eco-tourism and Argo-tourism Areas of Southern Part of Thailand - ทองขาว, คณพศ; รอดความทุกข์, วุฒิกรณ์; สุกระ, กชพรรณ; นิลแสง, อุบลรัตน์; จิตรแก้ว, ทัศนีย์; อัตตะ, ยุพยง; ศรีปล้อง, วาสินี; กอและ, กามัล (Journal of Health Science of Thailand, 2021)
This research aimed to investigate the chigger mite species, rat species as reservoir hosts, infection rate of scrub typhus and Orientia tsutsugamushi strains in rats obtained from ten surveyed areas of eco-tourism and agro-tourism areas in the south of Thailand. In each site, rats were trapped to collect the chigger mite. All samples were identified morphologically into species level. Rat serum samples were collected and the infection rate of scrub typhus was inspected using indirect immunofluorescence assay (IFA) technique. In addition, the liver and spleen of rats were chosen for detecting the O. tsutsugamushi strain using molecular technique. One hundred and sixty five out of 1,500 traps were successful for rat trapping (11.00%). Fourteen rat species, namely Rattus tanezumi, Maxomys surifer, Bandicota indica, Niviventer fulvescens bukit, Sundamys muelleri, R. tiominicus, M. whiteheadi, Hylomys suillus siamensis, Mus musculus castaneus, R. argentiventer, R. exulans, N. langbiansis, Leopoldamys sabanus and R. sladen were identified. Regarding the IFA technique, a total of 56 samples (33.94%) demonstrated as positive results. Herein, five rats including R. tanezumi, R. tiominicus, S. muelleri, B. indica and M. surifer exhibited immune response to scrub typhus. Concerning the examination of the O. tsutsugamushi strains from liver and spleen using PCR, nine of 111 samples (8.11%) held positive results and four strains of O. tsutsugamushi i.e. Kawasaki-related, Kato-related, Karp-related and TA763-related strains were encountered. Out of 165 rats caught, 127 rats could observe chigger mites. Consequently, the infestation rate was 0.77% of the total (5,387 chiggers). In terms of Chigger mite index, it valued 42.42 chigger mites collected and could be identified into 19 species. From this present study, three main chigger mites composing of Ascoschoengastia indica (42.75%), Leptotrombidium deliense (30.24%) and Blankaartia acuscutellaris (0.02%) could be seen in both surveyed areas. The most dominant chiggers were As. indica and L. delicense which could be found from R. tanezumi. Meanwhile, B. acuscutellaris was rarely seen in this time, suggesting that the information concerning scrub typhus together with the way of avoiding contact with infected chiggers should be publicized to the tourists who like traveling through a forest or the students who come to visit the area for exploring the culture and folkways in the countryside.